ANALYSIS OF EXTERNAL FACTORS ON RURAL ECOTOURISM ENTREPRENEURSHIP (CASE STUDY IN BOGOR REGENCY OF WEST JAVA) - Indra Setiawan Purba; Ricky Avenzora; Eva Anggraini; Dudung Darusman (APTKLHI, 2023)
The entrepreneurship aspect will determine the success of the development and development of rural ecotourism. Rural ecotourism products and services must be created and packaged by entrepreneurs in an attractive and highly competitive manner so that tourists are interested in consuming them. This study aimed to analyze the external factors that affect entrepreneurial capacity in rural ecotourism. The research location was in four tourist villages in Bogor Regency, namely Ciasihan, Sirnajaya, Watesjaya and Pabuaran Villages. Primary data was obtained through filling out a list of questions by respondents using a closed-ended questionnaire by applying the “one score one indicator scoring” system pattern . Data analysis was carried out in a quantitative descriptive manner based on the average value of each criterion/indicator. Analysis of causality between variables is carried out using logistic regression analysis. The results show that the external factors that significantly affect the performance of rural ecotourism entrepreneurship are dominated by social aspects (seven factors) and some aspects of the entrepreneurship ecosystem, namely 1) market, 2) finance and 3) business culture. The highest odds ratio is in the social interaction variable, which is 5.459, while the lowest odds ratio is in the group solidarity variable, which is 0.323. With the odds ratio of social interaction of 5.459, it can be interpreted that if social interaction in the tourist village increases, it will tend to cause the success in entrepreneurship 5.459 times higher than in the absence of social interaction.